« Dieu ne croit plus en nous. » Trois journaux personnels de l’exil dans la France des années troubles - Adelhakim Rezgui (Diasporas: Circulations, Migrations, Histoire)
This study draws on three diaries as historical case studies for understanding the mental universe of exile, and its various forms of expression, in France from the mid-1930s to the initial period of Occupation and Vichy rule. Paul Loffler’s diary opens a gateway into the experiences of an exile in asylum confronted by the increasing perilous years of 1933-1939. Monique d’Hesse’s diary offers insight into the exodus as a form of exile through the eyes of a child (May to August 1940) and the notebook of Abraham Dymentsztajn allows us to envisage internment in the Drancy ‘hunger camp’ as an exilic framework consisting of persecution (August to October 1941). While these documents are supposed to be the result of instantaneous writing, these ego-documents also constitute stimulating objects of historical memory.